A comparative study of Nd15Fe78B7 and Nd15Co78B7 systems: phase formations and coercivity mechanisms. (November 2022) - Wu, Yuye; Skokov, Konstantin P.; Schäfer, Lukas; Maccari, Fernando; Aubert, Alex; Rao, Ziyuan; Schweinar, Kevin; Gault, Baptiste; Xu, Hao; Jiang, Chengbao; Gutfleisch, Oliver
Abstract: Both Nd-Fe-B and Nd-Co-B nanocrystalline magnets exhibit coercivity above 1 T. While the microstructure and mechanism of the coercive force of Nd-Fe-B magnets are well known, the Nd-Co-B system is much less studied, and the microstructure and origin of the high coercive state in this material is not well understood. In this work, we selected Nd15 Fe78 B7 and Nd15 Co78 B7 alloys with simple and stable stoichiometries to reveal the similarities and differences between these two systems. For this study, melt-spun nanocrystalline ribbons, hot-compacted magnets and bulk materials crystallized from the amorphous precursor were used. The coercivity of Nd15 Fe18 B7 alloy is in the range of 0.9–1.7 T, while for Nd15 Co18 B7 it was of 0.5–1.0 T. Electron microscopy and atom probe tomography analyses indicate that, in contrast to conventional Nd15 Fe78 B7, where the ferromagnetic Nd2 Fe14 B phase is the dominant matrix phase and the Nd-rich phase distributes along the grain boundaries providing magnetic decoupling, the Nd15 Co18 B7 alloys comprise of three randomly redistributed exchange-coupled ferromagnetic phases: Nd2 Co14 B, NdCo5 and NdCo4 B. Single crystals of all constituent phases were grown and their spontaneous magnetization Ms and anisotropy constant K1 were determined. Using these measured intrinsic parameters and real nanostructure of Nd15 Fe78 B7 and Nd15 Co78 B7 alloys, micromagnetic simulations were carried out in order to reveal the differences in the coercivity mechanisms in these two distinctly different systems. Graphical abstract: Image, graphical abstract